Analysis of results of nonunion tibial fractures Ilizarov external fixation - Reddy, Pandillapalli Devanatha; Kumar, Koramutla Harsha (International Journal of Research in Orthopaedics, 2018)
Background: Tibia is most exposed bone in the body and vulnerable to trauma and therefore its fractures are common among the long bone fractures. Tibia is the common site of non-union in long bone fractures. Management of non-union in long bone fractures is a challenging problem for orthopedic surgeons. When the defect is more than 4 cm then it needs bone transport. Methods: Materials of this study comprised 20 cases of nonunions of tibia treated over 2½ years period from June 2006 to December 2009 in the Department of Orthopedics at Narayana Medical College, Nellore, Andhra Pradesh. This was a prospective study of nonunions of tibia treated by Ilizarov ring external fixators and incidental surgery. Results: Out of 20 tibial non-unions, in 15 patients the fixator has been removed. In 4 patients the fracture had united but the fixators are in situ and they are in consolidation phase and the remaining 1 patient is in various stage of follow up. The results of the 15 patients in whom the fixators have been removed are studied. The hospitalization time from 15 days to 120 days. The average hospital duration is 44.04 days. The total time ranged from 4 months to 15 months. Average time is 9.25 months. Conclusions: From this study we conclude that Ilizarov external fixator is a reliable, versatile and effective treatment for the treatment of tibia nonunion fractures.